Generation of noise-like pulse using nickel-based metal-organic framework saturable absorber - Murad, Amir; Mohd Yusoff, Norita; Ying, Josephine Chyi Liew; Eng, Khoon Ng; Alresheedi, Mohammed Thamer; Abas, Ahmad Fauzi; Mahdi, Mohd Adzir (Elsevier BV, 2023)
We experimentally demonstrate the generation of noise-like pulse (NLP) in an erbium-doped fiber laser using a metal-organic framework (MOF)-based saturable absorber. To fabricate the device, a tapered fiber was coated with MOF material, nickel 1,3,5-benzene-tricarboxylic acid (Ni-H3BTC) using a spin-coating method. The fabricated Ni-H3BTC-MOF saturable absorber exhibited 4.5% modulation depth and 30.3 MW/cm2 saturation intensity. A mode-locked erbium-doped fiber laser operated in the NLP regime was successfully achieved at 1564.90 nm central wavelength having 3-dB bandwidth of 19.96 nm, repetition rate of 9.02 MHz, and signal-to-noise ratio of 57.17 dB at 248 mW pump power. The characteristics of the NLP was confirmed by the spike width of 148 fs riding on a pedestal pulse duration of 26.67 ps. The estimated value of its damage threshold was experimented to be beyond 4.69 GW/cm2. These results infer that MOF-based saturable absorber can be an alternative material for the generation of ultrashort pulses.